2004
DOI: 10.1021/ja047896i
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Hydroxymethylation of Silicon Enolates Using an Aqueous Solution of Formaldehyde with a Chiral Scandium Complex

Abstract: Catalytic asymmetric hydroxymethylation of silicon enolates has been achieved. In this reaction, an aqueous solution of formaldehyde can be used to realize an easy and safe procedure, and high enantioselectivities have been obtained. This is the first example of catalytic asymmetric reactions in aqueous media with a chiral scandium complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(62 citation statements)
references
References 13 publications
3
59
0
Order By: Relevance
“…In an unrelated investigation, Kobayashi et al have reported a crystal structure of the scandium catalyst composed of ScBr 3 and bipyridine 2 which revealed a pentagonal-bipyramidal coordination geometry of the metal. [18] We successfully obtained a crystal structure of the corresponding eight-coordinate yttrium-bipyridine complex which exhibited the same sense of asymmetric induction and comparable level of enantioselectivity as the scandium catalyst (Figure 2). It clearly shows that the bipyridine ligand 2 was slightly twisted along the bipyridine axis (19.1°) and coordinated in a tetradentate fashion to the metal center.…”
Section: Mechanistic Considerationsmentioning
confidence: 92%
“…In an unrelated investigation, Kobayashi et al have reported a crystal structure of the scandium catalyst composed of ScBr 3 and bipyridine 2 which revealed a pentagonal-bipyramidal coordination geometry of the metal. [18] We successfully obtained a crystal structure of the corresponding eight-coordinate yttrium-bipyridine complex which exhibited the same sense of asymmetric induction and comparable level of enantioselectivity as the scandium catalyst (Figure 2). It clearly shows that the bipyridine ligand 2 was slightly twisted along the bipyridine axis (19.1°) and coordinated in a tetradentate fashion to the metal center.…”
Section: Mechanistic Considerationsmentioning
confidence: 92%
“…Instead, higher molecular weight (M w ) stilbenes and 2‐phenylnaphthalene ( 7 a ) were found instead (Table 1, entry 2). With Sc(OTf) 3 also being an excellent aldol condensation catalyst,14 7 a is likely formed by self‐condensation of 6 a , followed by intramolecular cyclization. These results clearly demonstrate the value of the tandem approach, with rapid removal of the reactive aldehydes by decarbonylation preventing undesired side reactions.…”
mentioning
confidence: 99%
“…The main selectivity issues associated with the Mukaiyama aldol reaction have been reported as being due to acid-catalysed hydrolysis. In molecular solvents the yield of aldol product formed is shown to be dependent on catalyst concentration, [29] silyl ether geometry [30] and concentration of water. [31] However, in these cases, even though the product yields were diminished there was no report of the formation of the self-condensation product that was obtained in ionic liquid, as described above.…”
Section: Resultsmentioning
confidence: 98%